Child Sexual Abuse in Indonesia: History and Challenge in Legal Perspective - Octaviana, Setyarini Nur (IJCLS (Indonesian Journal of Criminal Law Studies), 2019)
A case of child sexual abuse has become a common case among the community. The fundamental question was why the case it could not be eradicated and what is the basis of the person doing the Act of harassment was primarily in children. In the journal this time will discuss that question and analyze the appropriate punishment to the perpetrators so that deterrent, analyzes the impact of psychological casualties and challenge what we will encounter when trying to eradicate the case. Cases of sexual abuse have been around some of the last decade and became the most widely performed case, estimated the year 1970 was the initial disclosures of sexual abuse in children. It can be seen from the year the case was started and why we can't stop it the case was there first. Judith Lewis Herman in his book says that children who have become victims of abuse and trauma will tend to do it to others as adults later. It's like a cycle to continues, our task in tackling these cases is finding a way to keep people who have become victims can recover from trauma and break that cycle.